Digital Authoritarianism and Uyghur Identity Erasure as a Global Inflection Point - Maspul, Kurniawan Arif; Sopyan, Imam (Indonesian Journal Publisher, 2025)
In the shadow of global silence, the Uyghur crisis in Xinjiang emerges not merely as a regional atrocity, but as a harrowing blueprint for 21st-century digital authoritarianism. This paper confronts China’s systematic campaign of Uyghur identity erasure—through mass internment, linguistic imperialism, forced labor, and AI-powered surveillance—and positions it as a defining inflection point for the global human rights order. Drawing from Gramsci’s theory of cultural hegemony, Phillipson’s linguistic imperialism, and Wallerstein’s world-systems theory, the study constructs a powerful interdisciplinary analysis that connects cultural domination with economic coercion and digital repression. Through comparative historical parallels and contemporary legal frameworks, the paper argues that China’s actions constitute crimes against humanity and cultural genocide. Yet this is more than a diagnosis—it is a call to action. The study calls on the world community to move beyond rhetoric and toward coordinated justice by laying out a bold, multi-pronged opposition strategy that includes legal responsibility, economic sanctions, educational resilience, media activism, and cybersecurity. In doing so, it reframes Xinjiang not as China’s internal matter, but as the world’s moral reckoning. The survival of Uyghur identity, and the credibility of human rights in the digital age, depend on our collective will to confront this dystopian template of repression—and dismantle it.